Regulation of lactic acid concentration in its bioproduction from wheat flour. (September 2016) - Gonzalez, Karen; Tebbani, Sihem; Lopes, Filipa; Thorigné, Aurore; Givry, Sébastien; Dumur, Didier; Pareau, Dominique
Abstract: Lactic acid is an important molecule for biopolymer production that can be obtained by biological processes. This work deals with the control of the lactic acid concentration in its production bioprocess using wheat flour as substrate. An adaptive control strategy for the simultaneous saccharification, proteins hydrolysis and fermentation (SSPHF) continuous process of lactic acid production is proposed in order to regulate the lactic acid concentration to the target value. The latter is determined so that the lactic acid productivity is maximized. The control strategy effectiveness and robustness are illustrated by means of experimental results. Highlights: The lactic acid production is performed in continuous mode from wheat flour. A kinetic-free control law is developed, based on production rate estimation. The performance of the control law is assessed through experiments.